Activated flux induced Tungsten inert gas welding of Ferrous alloys - A Review. Issue 1 (1st July 2022) - Rakesh, N; Rameshkumar, K.
Abstract: Ferrous alloys are employed in a range of fields, including aerospace, construction, automobiles and chemical processing. One of the most used welding processes for the fusion of ferrous metals is gas tungsten arc (GTA) welding or Tungsten Inert Gas (TIG) welding. Due to the lower amount of penetration accomplished using only one pass, welding is less frequent in some industrial situations. Fluxes have been discovered to improve the penetration depth of GTA welding, resulting in increased productivity. The research on Activated flux induced TIG (A-TIG) welding of ferrous alloys is discussed in this publication. The effect of fluxes during TIG welding, the effect of weld parameters on weld morphology, and the usage of fluxes in dissimilar welds of ferrous alloys are all discussed in this study. The mechanisms involved in enhancement of penetration depth, the types of fluxes used, the effect of fluxes on mechanical properties and microstructures are discussed. The study also gives an insight on areas less explored.